Study of the Effect of Welding Current Variations on Joint Strength and Microstructure of Cracker Lontongan Chopper Machine - Rusdi, Firman Maulana; Istiqlaliyah, Hesti (Universitas Muhammadiyah Jakarta, 2023)
Welded joints in machine frame construction are prone to failure due to changes in material properties caused by the influence of heat, as well as the possibility of defects in welded joints. This is especially crucial in constructions subjected to dynamic loads, where the weld joint is a determining factor in the toughness of the material. This study aims to evaluate the microstructure, hardness, and tensile strength by applying variations in welding current in the Shielded Metal Arc Welding (SMAW) process. The research method included an experimental approach and literature study with careful observation. The findings of this study include: 1) The welding current strength significantly affected the microstructure arrangement of each tested specimen. 2) An increase in welding current resulted in an increase in the number and density of perlite structures in the Heat-Affected Zone (HAZ). In addition, an increase in welding current also resulted in an increase in hardness and tensile strength values. The average tensile strength successively increased from 90 A, 100 A, to 110 A, namely 320.11 MPa; 345.33 Mpa; 368.6 Mpa. 3) The results of statistical tests using the F-test on the tensile and hardness tests showed values of 0.023 and 0.040, respectively, indicating a significant difference in the hardness testing process with the application of current strengths of 90 A, 100 A, and 110 A. This research contributes to an in-depth understanding of the effect of welding current strength on the mechanical properties of materials, with important implications for improving the reliability of welded joints in machine construction.